2006
DOI: 10.1007/s00064-006-1185-2
|View full text |Cite
|
Sign up to set email alerts
|

Die arthroskopische Meniskusnaht

Abstract: The healing rate for knee joints with stable ligaments and an isolated meniscal tear is between 50% and 75%. In cases with simultaneous ACL (anterior cruciate ligament) plasty, the healing rate is > 75%; for unstable knee joints it is < 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Bei Meniskusläsionen gelten folgende Therapierichtlinien [11]: F Bei peripheren Längsrissen im Vorderhorn und in der Pars intermedia erfolgt eine Refixation mittels "Outside-in-Naht". F Im Bereich des Hinterhornes erfolgt eine "All-inside-Naht".…”
Section: Meniskusläsionenunclassified
“…Bei Meniskusläsionen gelten folgende Therapierichtlinien [11]: F Bei peripheren Längsrissen im Vorderhorn und in der Pars intermedia erfolgt eine Refixation mittels "Outside-in-Naht". F Im Bereich des Hinterhornes erfolgt eine "All-inside-Naht".…”
Section: Meniskusläsionenunclassified
“…As a movable articular surface, the menisci play an important role in the load distribution in the knee joint [26]. Other functions of the menisci include stabilization and lubrification of the knee joint [27]. Various studies have shown that the removal of meniscal tissue leads to osteoarthritis in the long-term [6,7,34].…”
Section: Introductionmentioning
confidence: 99%
“…Meniscal repair is a procedure for which various surgical techniques have been described: open and arthroscopic procedures, inside-out sutures, outside-in sutures, and allinside sutures [27,32]. Various factors have been identified that influence the success of meniscal repair (joint stability, associated ACL reconstruction, age, tear shape, methods of stimulating healing) [16,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In einem nicht unerheblichen Teil (etwa 10-25%) finden sich bei Spaltimpressions-und Luxationsfrakturen am Tibiakopf begleitende relevante Meniskusläsionen [1,4,10,25]. Bei Letzteren gelten folgende Therapierichtlinien: Periphere Längsrisse im Vorderhorn und in der Pars intermedia können mittels Inside-out-/Outside-in-Naht refixiert werden, im Bereich des Hinterhorns sind Allinside-Nähte gut geeignet, und komplexe Läsionen im avaskulären Anteil werden in der Regel teilreseziert [23,25].…”
unclassified